Perception and Acceptance of COVID-19 Vaccine Among Nurses in Jordan - Khulud Ahmad Rezq RN.BSN, MSN, PhD; Abeer Hesham AI_Zaghmouri RN, BSN, MSN (SAGE Publishing, 2023)
Introduction Vaccination against coronavirus disease (COVID-19) is a key factor in protecting vulnerable populations, reducing healthcare burdens, and mitigating the economic and social impacts of the pandemic. Objective This study aims to investigate Jordanian nurses' perceptions, acceptance, and factors affecting their decisions toward the COVID-19 vaccines. Methods In this study, we conducted a cross-sectional design. Data have been investigated between July 1, 2021 and August 30, 2021. Nurses at three private hospitals in Jordan were surveyed online. The online survey, created using Google Forms, was distributed to nurses via email and social media sites (e.g., WhatsApp and Facebook). Participants were eligible if they were a RN nurse and/or nursing assistance, and had access to the internet via computer and/or smartphone. Results Out of 189 responses, 50.6% agreed to receive the COVID-19 vaccine, while 25.5% disagreed, and 23.9% were undecide to receive the vaccine. A large proportion (84.66%) of the respondents had a negative perception toward the vaccine, while only a small minority (15.34%) had a positive perception of it. The older nurses, those with more experience, and those with a higher level of education were more likely to accept the vaccine, with acceptance rates of 56.1%, 54.8%, and 63.9%, respectively. Conclusion Of the nurses surveyed, 84.66% had a negative perception of the COVID-19 vaccine, and only 50.6% reported that they would be willing to get vaccinated. It is crucial to address the concerns and reduce apprehension among nurses about the vaccine. Efforts to increase awareness about the importance of vaccination in controlling the disease through workshops and online meetings are needed.